Increasing the efficiency of knowledge transfer in an Italian tourism system: a network approach. Issue 13 (3rd July 2022) - Valeri, Marco; Baggio, Rodolfo
ABSTRACT: Efficient transferring information and knowledge play a fundamental strategic role in a tourism system. This is especially important in critical times where efficient collaboration practices and a fluid flow of ideas is essential for the performance and the growth of the entire tourism industry. Here we use the methods of network science for increasing our awareness of the different collaborative structures and the potential information and knowledge flows across them. Intermediaries play a fundamental strategic role for the whole tourism domain and the good functioning this system is crucial for the social and economic development of tourism activities. The paper builds on previous research on the subject and takes as unit of analysis the Italian travel agencies and tour operators. Numerical simulations allow to build scenarios that improve the understanding of the Italian tourism intermediaries knowledge network and can be used to devise policies that tend to a more efficient and innovative functioning of the sector. The findings show how even limited structural changes in the system sensibly improve its efficiency and the capability to exchange information and knowledge.